Allosteric Modulation of the Sigma-1 Receptor Elicits Antipsychotic-like Effects. (1st December 2021) - Chen, Jiali; Li, Guangying; Qin, Pingping; Chen, Jiaojiao; Ye, Na; Waddington, John L; Zhen, Xuechu
Abstract: Allosteric modulation represents an important approach in drug discovery because of its advantages in safety and selectivity. SOMCL-668 is the first selective and potent sigma-1 receptor allosteric modulator, discovered in our laboratory. The present work investigates the potential therapeutic effects of SOMCL-668 on phencyclidine (PCP)-induced schizophrenia-related behavior in mice and further elucidates underlying mechanisms for its antipsychotic-like effects. SOMCL-668 not only attenuated acute PCP-induced hyperactivity and PPI disruption, but also ameliorated social deficits and cognitive impairment induced by chronic PCP treatment. Pretreatment with the selective sigma-1 receptor antagonist BD1047 blocked the effects of SOMCL-668, indicating sigma-1 receptor-mediated responses. This was confirmed using sigma-1 receptor knockout mice, in which SOMCL-668 failed to ameliorate PPI disruption and hyperactivity induced by acute PCP and social deficits and cognitive impairment induced by chronic PCP treatment. Additionally, in vitro SOMCL-668 exerted positive modulation of sigma-1 receptor agonist-induced intrinsic plasticity in brain slices recorded by patch-clamp. Furthermore, in vivo lower dose of SOMCL-668 exerted positive modulation of improvement in social deficits and cognitive impairment induced by the selective sigma-1 agonist PRE084. Also, SOMCL-668 reversed chronic PCP-induced down-regulation in expression of frontal cortical p-AKT/AKT, p-CREB/CREB and BDNF in wide-type but not sigma-1 knockout mice. Moreover, administration of the PI3K/AKT inhibitor LY294002 abolished amelioration by SOMCL-668 of chronic PCP-induced schizophrenia-related behaviors by inhibition of BDNF expression. The present data provide initial, proof-of-concept evidence that allosteric modulation of the sigma-1 receptor may be a novel approach for the treatment of psychotic illness.